2009
DOI: 10.1007/s10695-009-9370-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of monoamine neurotransmitters in fighting fish Betta splendens exposed to waterborne phytoestrogens

Abstract: Endogenous estrogens are known to affect the activity of monoamine neurotransmitters in vertebrate animals, but the effects of exogenous estrogens on neurotransmitters are relatively poorly understood. We exposed sexually mature male fighting fish Betta splendens to environmentally relevant and pharmacological doses of three phytoestrogens that are potential endocrine disruptors in wild fish populations: genistein, equol, and β-sitosterol. We also exposed fish to two doses of the endogenous estrogen 17β-estrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 89 publications
(97 reference statements)
1
17
0
1
Order By: Relevance
“…4). Levels of 5-HT and 5-HIAA were comparable to those in other studies for fish of comparable size to A. burtoni (Clotfelter et al, 2010;Larson et al, 2003) and did not differ between social groups in any of the brain regions ; all MWU) (supplementary material Fig. S2).…”
Section: Serotonin Turnover Varies By Social Status In Discrete Brainsupporting
confidence: 82%
“…4). Levels of 5-HT and 5-HIAA were comparable to those in other studies for fish of comparable size to A. burtoni (Clotfelter et al, 2010;Larson et al, 2003) and did not differ between social groups in any of the brain regions ; all MWU) (supplementary material Fig. S2).…”
Section: Serotonin Turnover Varies By Social Status In Discrete Brainsupporting
confidence: 82%
“…Serotonin is well known for its role in modulating social behavior, aggression and sex change in teleost fishes [76], [77]. In addition, serotonin levels are sensitive to CRF activity, and seem to play a role in modulating anxiety-like behavior in fish [21].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is quite worrying since when SITO concentrations surpass 10,000 ng L −1 it can act as an endocrine disrupter for aquatic animals (Clotfelter et al 2010). …”
Section: −1mentioning
confidence: 99%
“…Despite the high water turnover at each tide, several studies reported eutrophication and hypoxia, mainly in summer at some spots of the lagoon (Newton and Mudge 2005;Newton et al 2010); however, no information exists about the presence of either phytoestrogens or the annual fluctuation patterns of sitosterol. These compounds in spite of being of natural/vegetal sources, in high amounts phytoestrogens and sitosterol, are known to act as endocrine disrupter compounds (EDCs; Hoerger et al 2009;Clotfelter et al 2010). Thus, beyond the last compounds, the present study aimed to provide the first data for the Ria Formosa Lagoon about the levels of several of the most concerning worldwide anthropogenic/industrial EDCs such as estradiol, estrone, ethynylestradiol, 4-n-octylphenol, 4-toctylphenol, nonylphenol, several polyethoxylates (4-octylphenol monoethoxylate, 4-octylphenol diethoxylate, 4-nonylphenol monoethoxylate, 4-nonylphenol diethoxylate), and bisphenol A.…”
Section: Introductionmentioning
confidence: 99%